Creative fashion illustration : how to develop your own style - McKenzie, Stuart (Illustrator) (London ; Bloomsbury, 2014)
"Fashion illustration is skilful and inventive, and the best fashion illustrators can fulfil a brief creatively using their own unique approach. Visually-led and extremely accessible, this book is the go-to resource for anyone wanting to develop their own style. Easy-to-follow exercises are designed to build confidence and encourage experimentation as readers develop essential skills and learn simple and effective tips and tricks. With concise, accessible chapters on topics such as proportion, movement, line, shape and volume as well as sections on tricky areas such as hands and feet, Creative Fashion Illustration is essential reading for anyone looking to enhance their basic drawing skills. Whether coming to fashion illustration for the very first time, a student looking to develop their techniques and expand their portfolio, or even a more experienced illustrator looking for fresh ideas, this book is the ideal guide to imaginative fashion illustration that will stand out from the crowd"--
Line -- Silhouette -- Light & shade -- Collage -- Fabrics, Texture, pattern -- Drawing design details -- Exaggeration -- Drawing from life -- Movement -- Proportion -- Faces -- Hands & feet -- Flat drawings: communication designs -- Showcase -- Inspiration -- Toolbox.
Keywords: Fashion drawing; DESIGN / Fashion; DESIGN / Graphic Arts / Illustration